G9a and DNMT1 inhibition modulates CDKN1A promoter methylation and the cell cycle leading to improvement in kidney fibrosis - Yang, Yuanyuan; Zhou, Zijian; Wang, Lujia; Gao, Peng; Wu, Zhong (Biochimica et biophysica acta. General subjects, 2023)
Epigenetic mechanisms, including histone and DNA methylation, play a key role in kidney fibrosis, but the precise mechanism remains unclear. Concerted action between histone and DNA-methyltransferases like G9a and DNMT1 is a common theme in gene expression regulation. We investigated the role of G9a and DNMT1 in kidney fibrosis pathogenesis and aimed to elucidate key G9a and DNMT1 targets contributing to kidney fibrosis maintenance. G9a and DNMT1 were detected in human fibrotic kidneys, UUO mouse kidneys, and TGFβ1-induced HK-2 cells. G9a and DNMT1 expression was knocked down by siRNA or inhibited with CM272 in HK-2 and UUO mouse, and transcriptomic responses to CM272 were examined. Antifibrogenic activity and safety of CM272 were studied in UUO mouse. Cell cycle were analyzed with flow cytometry. Gene expression regulation was analyzed by chromatin immunoprecipitation and methylation-specific PCR. G9a and DNMT1 were overexpressed in human fibrotic kidneys, UUO mouse kidneys, and TGFβ1-induced HK-2 cells. G9a/DNMT1 inhibition potently alleviated fibrosis in vitro and vivo. G9a/DNMT1 inhibition reduced the expression of E2F targets and altered the methylation status of CDKN1A leading to the attenuated cell-cycle arrest. TGFβ1-induced overexpression of G9a or DNMT1 resulted in the enrichment of H3K9me2 and 5-methylcytosine at CDKN1A promoter. Our data link G9a and DNMT1 to CDKN1A regulatory function and kidney fibrosis. Combined targeting G9a and DNMT1 could be a promising strategy for the treatment of kidney fibrosis. •Together with DNMT1, G9a is overexpressed in human fibrotic kidneys, UUO mouse kidneys, and TGFβ1-induced HK-2 cells.•G9a/DNMT1 inhibition profoundly affects the fibrogenic activation of kidney myofibroblasts and cell cycle.•Reduced CDKN1A in response to renal fibrosis is linked to increased methylation of H3K9 and cytosine at the promoter region.